The genus Megastylus Schiødte (Hymenoptera, Ichneumonidae, Orthocentrinae) in China with a key to the species of China and Oriental Region - Zhang, Shu-Jie; Zhou, Qing; Li, Tao; Sheng, Mao-Ling (Zootaxa, 2022)
Three new species of Megastylus Schiødte, 1838 (Ichneumonidae, Orthocentrinae), M. (Dicolus) mentouense Sheng & Li, sp. nov. collected from Mentougou, Beijing, M. (D.) flavicornis Sheng & Li, sp. nov. from Shennongjia National Natural Reserve, Hubei and M. (Megastylus) yindianense Sheng & Li, sp. nov. from Minquan, Henan, are described and illustrated. A taxonomic key to the species of Megastylus known from China and the Oriental Region is provided.